Black and blue : inside the divide between the police and Black America - Pegues, Jeff, 1970- (Amherst, NY : Prometheus Books, 2017)
"The recent killings in Dallas, Baton Rouge, Ferguson, and elsewhere are just the latest examples of the longstanding rift between law enforcement and people of color. In this revealing journey to the heart of a growing crisis, CBS News Justice and Homeland Security Correspondent Jeff Pegues provides unbiased facts, statistics, and perspectives from both sides of the community-police divide. Pegues has rare access to top law enforcement officials throughout the country, including FBI Director James Comey and police chiefs in major cities. He has also interviewed police union leaders, community activists, and others at the heart of this crisis--people on both sides who are trying to push American law enforcement in a new direction. How do police officers perceive the people of color who live in high-crime areas? How are they viewed by the communities that they police? Pegues explores these questions and more through interviews not only with police chiefs, but also officers on the ground, both black and white. In addition, he goes to the front lines of the debate as crime spikes in some of the nation's major cities. What he found will surprise you as police give a candid look at how their jobs have changed and become more dangerous. Turning to possible solutions, the author summarizes the best recommendations from police chiefs, politicians, and activists. Readers will not only be informed but learn what they can do about tensions with police in their communities"--
"A CBS correspondent presents an objective overview of the challenges confronting law enforcement as it attempts to reform in the wake of the unrest sparked by the police shootings in Ferguson and other communities"--
Foreword / by Charles Ramsey -- Preface -- Reform is in the air -- Broken windows -- Three days and seven dead -- Thin blue line -- "Something is happening in America" -- Livestock -- Ghost skins -- Sixteen shots -- Executive Order 13684 -- Truth and reconciliation -- Fear of the badge -- Policing system is broken -- The recruits -- The race card -- Dallas -- Treat people as you want to be treated -- Code of silence -- Train to kill -- The magic wand -- "Broken windows is not broken" -- "Sixteen shots and a cover-up!" -- Coming clean -- Afterword.
Includes index.
Includes bibliographical references (pages 241-262) and index.
Keywords: Police -- United States; Law enforcement -- Moral and ethical aspects -- United States; Police brutality -- United States; Police misconduct -- United States; African Americans -- Civil rights; Police-community relations -- United States; Political science -- Political Freedom & Security -- Law Enforcement; SOCIAL SCIENCE -- Criminology